Relationships between body size, weight, condition and fecundity of the threatened fish puntius ticto (Hamilton, 1822) in the Ganges River, Northwestern Bangladesh - Yeamin Hossain .Md,; Mosaddequr Rahman .Md,; Elgorban M. Abdallah, (Universiti Kebangsaan Malaysia, 2012)
The ticto barb Puntius ticto (Hamilton 1822) is a small, indigenous fish species of Bangladesh that is widely distributed in the natural waters of Asian countries. This study describes the relationships between body size, weight, condition (Fulton’s, KF; allometric, KA, KR; and relative weight, WR) and fecundity of the threatened species P. ticto from the Ganges River, northwestern Bangladesh. A total of 24 mature female specimens were collected by the traditional fishing gears from March to August 2006. For each individual, total (TL), fork (FL), standard length (SL), and ovary length (OL) were measured by digital slide calipers, while body (BW) and ovary weight (OW) were taken by a digital balance. Total fecundity (FT) of each female was calculated as the number of eggs found in each ovary, whereas relative fecundity (FR) was the number of eggs per gram of fish weight. The results showed that TL of P. ticto varied from 9.10 to 10.80 cm, with calculated mean ± SD as 9.77±0.57 cm. Body weights extended from 14.00 to 24.00 g, with calculated mean ± SD as 17.83±3.39 g. The mean FT was 2586±700 and ranged from 1611 to 4130. BW was more significantly correlated with total fecundity (r2>0.633; p<0.001) than various other body metrics. The results also indicated significant correlation between length-weight (df=22, t-test≥8.86, p<0.001); FT -KF (rs=0.473; p=0.019), FT-KA (rs=0.502; p=0.012), and FT-WR (rs=0.483; p=0.016), but insignificant correlations were found between FT-GSI (rs=0.309; p=0.141) and FR-with various other body metrics. The knowledge of fecundity would be useful to impose adequate regulations for the conservation of this threatened species in the Ganges River and nearby areas of Bangladesh.